2018
DOI: 10.1002/er.4132
|View full text |Cite
|
Sign up to set email alerts
|

Research on the hot surface ignition of hydrogen-air mixture under different influencing factors

Abstract: Summary To further reveal the pre‐ignition characteristics of hydrogen internal combustion engine, the effect of hot surface characteristic parameters on the ignition characteristics of hydrogen‐air mixture was investigated in this research. Based on the prototype of the constant volume combustion bomb with an overhead glow plug, the duration from the heating of the hot surface to the combustion of hydrogen‐air mixture, the so‐called heating duration, was firstly researched under different fuel‐air equivalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It can be seen that the variation of ignition delay times is not notable with the equivalence ratio increasing when initial temperatures are lower than 650 K and higher than 1000 K; however, at initial temperatures of 650 K to 1000 K, the equivalence ratio has a significant effect on ignition delay times. Furthermore, when the initial temperature is lower than 1200 K, the ignition delay time decreases as the equivalence ratio increases, which is consistent with the results in reference . However, at the initial temperature of higher than 1250 K, the higher the equivalence ratio is, the longer the ignition delay time is.…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that the variation of ignition delay times is not notable with the equivalence ratio increasing when initial temperatures are lower than 650 K and higher than 1000 K; however, at initial temperatures of 650 K to 1000 K, the equivalence ratio has a significant effect on ignition delay times. Furthermore, when the initial temperature is lower than 1200 K, the ignition delay time decreases as the equivalence ratio increases, which is consistent with the results in reference . However, at the initial temperature of higher than 1250 K, the higher the equivalence ratio is, the longer the ignition delay time is.…”
Section: Resultssupporting
confidence: 91%
“…Duan and Liu 39 investigated the hydrogen-fueled engine combustion performance and 49 (2008) the hydrogen-fueled engine used in the experiment is modified from a three-cylinder and twostroke engine; the cylinder × diameter stroke: 61 × 61.5, emission capacity 539 cc, half ball firebox, compression ratio 6.9:1 signal processing methods wavelet analysis is effective for diagnosing abnormal combustion Yang et al 50 (2010) a single-cylinder, four-stroke hydrogen-fueled engine; the engine is water-cooled horizontal type; its displacement is 482 cm 3 , bore is 85 mm, stroke is 85 mm, compression ratio can be changed from 4.8 to 7.93 hemisphere signal processing and control model ignition timing and excessive air ratio were the essential factors affecting rate of pressure rise Yang et al 52,53 (2012) as the above control model method the propagation speed of laminar flames is related to the state and operating parameters of hydrogen fuel engines; among them, temperature, pressure, boost rate, and excess air ratio have the greatest impact on abnormal combustion Qin et al 58 (2017) as the above CFD methods low-temperature combustion technology can reduce the rough working characteristics of hydrogen internal combustion engines Gao et al. 55 (2014) as the above, but using two valve intakes CFD methods the impact of different inlet ports on abnormal combustion Yang et al 60 (2022) as the above, but using a four-valve structure CFD and data processing verified the applicability of AHP method in the study of hydrogen injection angle and flow rate on early ignition and tempering of hydrogen internal combustion engines Duan et al 54 (2013) a 4-cylinder, 1.998 L, PFI hydrogen internal combustion engine with intake port injection, with a bore of 86 mm and a stroke of 86 mm CFD methods optimizing the angle of hydrogen injection can effectively suppress backfire and investigate the reasons for abnormal combustion in hydrogen internal combustion engines with different loads Liu et al 56 (2014) as the above experimental study experimental evidence on the causes of abnormal combustion in hydrogen internal combustion engines with different loads Luo et al 57 (2016) as the above experimental and numerical model analysis in the PFI hydrogen internal combustion engine, the effects of ignition timing and backfire on combustion knock were explained Yang et al 59 (2018) not mentioned experimental study explored the importance of the influence of various parameters on the hot spots of hydrogen internal combustion engines Dang et al. 61 (2022) a 539 cm 3 hydrogen internal combustion engine with a hemispherical combustion chamber, with a cylinder diameter of 61 mm and a piston stroke of 61 emission characteristics based on a PFI-HICE test system equipped with a hot EGR system.…”
Section: A Study Related To the Structural Form Of Different Hicesmentioning
confidence: 99%
“…They pointed out that low-temperature combustion, which was achieved through enhancing high specific-heat components and reducing oxygen concentration of in-cylinder charge, can effectively control the combustion reaction velocity, suppress the preignition and harsh combustion, and reduce NO pollutant in hydrogen-fueled engine. To explore the preignition of HICE caused by hot spots in depth, Yang et al 59 investigated the influence regularity of feature parameters of a hot surface (especially temperature and area of the hot surface) on the duration of heat of a hot surface. Results from simulations revealed that the duration of heat could be reduced as the temperature and area of the hot surface increased, but the decreasing amplitude was gradually reduced, as shown in Figure 10 .…”
Section: Current Status Of Research On Different Topics Of Hices In C...mentioning
confidence: 99%